Research on Mode Superposition Damage Imaging Method for Isotropic Materials - FEI, Yue; WANG, Zi-ping; ZHOU, Ai; LI, Bing-qian (2020 15th Symposium on Piezoelectrcity, Acoustic Waves and Device Applications (SPAWDA), 2021)
Ultrasonic guided wave phased array technology is widely used in the damage detection of isotropic media, and its multi-mode problem leads to the complexity of signal processing, which affects the final imaging accuracy. In this paper, a single mode separation algorithm is constructed in the frequency wave number domain.. The single mode is stripped together with the phased array imaging method. Finally, the data fusion method is used to achieve the superposition of different modes. Firstly, according to the simulation results, the appropriate excitation frequency is selected to generate multi-mode Lamb wave, and the rectangular array is used to collect the signal in space-time domain. 3-D Fourier transform is used to transform the time-space domain signal into frequency wavenumber domain, and a 3-D window function is constructed to separate the A 0 and S 0 modal damage reflection waves. The signal is restored to space-time domain by three-dimensional inverse Fourier transform. Then, the CSM (Common Source Method) imaging algorithm in time domain and frequency wavenumber domain of phased array is combined to realize the damage imaging of single mode. Finally, the superposition results of two different modes are achieved by data fusion method. The results show that the result of modal superposition is better than that of the single mode imaging.